2010
DOI: 10.1021/ac9020769
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Graphite Target for Biological/Biomedical/Environmental Applications of 14C-Accelerator Mass Spectrometry

Abstract: Catalytic graphitization for 14C-accelerator mass spectrometry (14C-AMS) produced various forms of elemental carbon. Our high-throughput Zn reduction method (C/Fe = 1:5, 500 °C, 3 h) produced the AMS target of graphite-coated iron powder (GCIP), a mix of nongraphitic carbon and Fe3C. Crystallinity of the AMS targets of GCIP (nongraphitic carbon) was increased to turbostratic carbon by raising the C/Fe ratio from 1:5 to 1:1 and the graphitization temperature from 500 to 585 °C. The AMS target of GCIP containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…The production of high quality, uniform graphite targets, suitable for the AMS ion source, is important for the optimal performance of any AMS system. The quality of the graphite influences the level of background contamination, the mass fractionation, and the beam current (Santos et al, 2007c, Kim et al, 2010.…”
Section: Graphitization and Ams Measurementsmentioning
confidence: 99%
“…The production of high quality, uniform graphite targets, suitable for the AMS ion source, is important for the optimal performance of any AMS system. The quality of the graphite influences the level of background contamination, the mass fractionation, and the beam current (Santos et al, 2007c, Kim et al, 2010.…”
Section: Graphitization and Ams Measurementsmentioning
confidence: 99%
“…For identification of peaks, the standard reference spectra of Fe 3 C and graphite are also shown, as circles and triangles, respectively, in the GP spectrum (Downs and Hall-Wallace 2003). Kim et al (2010) measured the PXRD spectra of graphitization products with varying C/Fe mass ratio (1:1, 1:5, 1:10, and 1:15) at different temperatures (400, 500, 525 and 585°C) (Kim et al 2010). Their PXRD spectrum of the graphitization product with 1:1 (C/Fe) mass ratio, prepared at 585°C closely resembles that of the samples we prepare at 600°C (~1:1 C/Fe).…”
Section: Discussionmentioning
confidence: 99%
“…34 Catalytic graphitization methods for bio-14 C-AMS are known to produce a fullerene "graphite," 42,43 morphologically similar to lamentous graphite. 40 Recently, Kim et al 57,58 reported the morphological, chemical, and physical characteristics of graphite produced using their septa-sealed vial method. 37 Aer graphitization, the carbonaceous sample of interest was converted to a semi-ordered graphite-like material rather than a single graphite crystal.…”
Section: C-ams Applicationsmentioning
confidence: 99%
“…In addition, they reported that the degree of graphite crystallinity did not affect 14 C-AMS analysis, including C À ion currents, bulk isotopic fractionation (d 13 C), and Modern value. 57 The ratio of carbon (graphite or graphitelike) to iron powder (used as a thermal/electrical conductor during ionization) in the graphitized sample was the most critical factor affecting reliable C À ion currents, which are required for accurate, precise, and reproducible 14 C-AMS measurements. 57 Sample type, size, graphitization yield, and other considerations for bio-14 C-AMS Table 3 shows the common biological samples used in bio-14 C-AMS and their carbon contents.…”
Section: C-ams Applicationsmentioning
confidence: 99%